2018
DOI: 10.3390/ijerph15071493
|View full text |Cite
|
Sign up to set email alerts
|

Oral Symptoms and Oral Health-Related Quality of Life in People with Rare Diseases in Germany: A Cross-Sectional Study

Abstract: Background: The aim of this study was to collect information on oral health-related quality of life (OHRQoL) in people with rare diseases. Methods: A questionnaire comprising free text questions and the German version of the standardized Oral Health Impact Profile-14 (OHIP-14) questionnaire on OHRQoL was developed. All participants who indicated oral symptoms in the questionnaire were included in a cluster analysis. Different cluster analyses were performed (Ward’s, k-Means) to find symptom profile groups in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 28 publications
2
24
0
1
Order By: Relevance
“…Parents and caregivers of individuals with MPS perceive this impact on OHRQoL, because the oral conditions of individuals with MPS are worse (hygiene, greater presence of malocclusion, greater experience with caries) than individuals without MPS. 7,14 According to the literature, GAGs progressively accumulate in bones, cartilage, muscles and ligaments, generating an inflammatory process and tissue damage that result in functional limitations and pain. 13,16,17,8 A study conducted in Norway involving 209 parents of children and adolescents (six to 18 years) with rare congenital disorders showed that health-related quality of life was lower among the children with rare disorders than children from the general population; the greatest reduction in quality of life was found for physical functioning, whereas the smallest was found for emotional functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents and caregivers of individuals with MPS perceive this impact on OHRQoL, because the oral conditions of individuals with MPS are worse (hygiene, greater presence of malocclusion, greater experience with caries) than individuals without MPS. 7,14 According to the literature, GAGs progressively accumulate in bones, cartilage, muscles and ligaments, generating an inflammatory process and tissue damage that result in functional limitations and pain. 13,16,17,8 A study conducted in Norway involving 209 parents of children and adolescents (six to 18 years) with rare congenital disorders showed that health-related quality of life was lower among the children with rare disorders than children from the general population; the greatest reduction in quality of life was found for physical functioning, whereas the smallest was found for emotional functioning.…”
Section: Discussionmentioning
confidence: 99%
“…7 ,8,9,10,11 Oral health plays a fundamental role in the lives of individuals with MPS, as oral diseases may result in infection as well as nutritional, respiratory, chewing and speech problems, compounding their already severely weakened state of general health. 5,11,12,13,14 Oral health-related quality of life (OHRQoL) regards the impact of oral problems on aspects of daily living. 15 The magnitude of impact in terms of frequency, severity or duration can affect an individual's perception of his or her life in general.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in patients with orthodontically relevant symptoms, such as dysgnathia or oligodontia, these not only can give a clue to the underlying disease, but also indicate serious impact on the oral health-related quality of life [21]. Research has also shown that patients with syndromic oligodontia which had not been linked to a rare disease in the first place reported substantially worse outcomes [22].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, different researcher concentrates their work in the dental field to predict the oral disease in an earlier stage. Sabrina Wiemann et al, [18] were analyzing the oral health and hygiene to predict the various diseases from German people using clustering techniques. Initially, effective questionnaires are created, which is asked to the patient for collecting the dental information.…”
Section: Related Workmentioning
confidence: 99%
“…The created set consists of 484 questionnaires, which being examined in terms of applying the oral hygiene impact profile factor 14, and similar information are grouped using clustering techniques. In this work, [18] [20] were diagnosing oral cavity related autoimmune disease using clinical analysis. First, the dental information is collected with the help of dentists, which are fed into autoimmune pathologies to get the knowledge of the disease.…”
Section: Related Workmentioning
confidence: 99%